Computer security basics - Lehtinen, Rick (O'Reilly & Associates, 2006)
For anyone involved with computer security, including security administrators, system administrators, developers, and IT managers, this book offers an overview of the security concepts you need to know, including access controls, malicious software, security policy, cryptography, biometrics, as well as government regulations and standards.